A Walk through Graduate Education Selected Papers and Speeches of Jules B. LaPidus, President of the Council of Graduate Schools, 1984-2000 - Council of Graduate Schools, Washington, DC.; Hamblin, Jane A.; Council of Graduate Schools, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This book was created to honor Jules B. LaPidus, retiring president of the Council of Graduate Education, and to preserve his writings and speeches. The papers and speeches of Part 1 show how the author addressed the topical issues of graduate education, moving from observation to direction on research, funding, and preparation of faculty. Part 2 contains speeches and one additional paper aimed at students. Following a preface in which the Board of Directors of the Council of Graduate Schools express their appreciation of LaPidus, these papers are presented: (1) "A Christmas Parable"; (2) "The Professionalization of the Master's Degree"; (3) "Research and the University"; (4) "The Concern for Quality and the Quality of Concern"; (4) "Graduate Education: Perturbations and Prospects"; (5) "Humanizing Graduate Studies in the Humanities"; (6) "The Graduate Pipeline"; (7) "The Strain of Quality"; (8) "Preparing Faculty: Graduate Education's Role"; (9) "Great Expectations: The Role of the American University in the 21st Century"; (10) "Communities of Scholars: Research in the University"; (11) "Some Thoughts on the Relationship between Research and Research Universities"; (12) "A Place for Learning: The University and Society"; (13) "Deja Vu All Over Again"; (14) "Scholarship and Research: Graham's Law Revisited"; (15) "Ph.D.s and Jobs: A World They Never Made"; (16) "Doctoral Education: Preparing for the Future"; (17) "If We Want Things To Stay as They Are, Then Things Will Have To Change"; (18) "The Role of Theses and Dissertations as Independent Works of Scholarship"; (19) "Some Globalization Aspects of Graduate Education"; (20) "Broadening the Scope of Graduate Education: Postbaccalaureate Futures"; (21) "Is What's Past (or Post) Still Prologue? Or 'You Used To Be My Used To Was But Now You Ain't No More'"; (22) "Numbers Last: A Proposal for Improving Departmental or Program Based Graduate Admissions"; (23) "A Passion for Graduate Education"; (24) "An Atlas for Scholars"; (25) "Reducing the Deficit"; and (26) "The Corner of Your Eye." An appendix contains four tributes to Jules B. LaPidus by colleagues. (Contains 125 references.) (SLD)
Availability: Council of Graduate Schools, Inc., One Dupont Circle, NW, Suite 430, Washington, DC 20036-1136 ($30). Tel: 202-223-3791; Web site: http://www.cgsnet.org.
Sponsoring Agency: Educational Testing Service, Princeton, NJ. Graduate Record Examination Board Program.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; Educational Finance; Educational Research; Graduate Students; Graduate Study; Higher Education; Scholarship; Teacher Education; Books; Collected Works, General